2016
DOI: 10.1007/s00167-016-4363-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute ACL reconstruction in patients over 40 years of age

Abstract: Cohort study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…However, return to specific preinjury sports has not been investigated in any of the included studies. A recently published article comparing acute ACL reconstruction in patients older and younger than 40 years of age demonstrated that, 2 years postoperatively, both age groups returned to their preinjury activity level and did not significantly change their activity with respect to pivoting sports and sports frequency 35. Barrett et al 6 showed that the Tegner activity level is not adequately designed to investigate return to sport.…”
Section: Discussionmentioning
confidence: 99%
“…However, return to specific preinjury sports has not been investigated in any of the included studies. A recently published article comparing acute ACL reconstruction in patients older and younger than 40 years of age demonstrated that, 2 years postoperatively, both age groups returned to their preinjury activity level and did not significantly change their activity with respect to pivoting sports and sports frequency 35. Barrett et al 6 showed that the Tegner activity level is not adequately designed to investigate return to sport.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-one studies (15%) did not use time as a RTS criterion. Eighteen studies (8%) reported a time frame for RTS clearance; seven studies [18][19][20][21][22][23][24] (3%) reported a range (eg, RTS at 6-12 months) and 11 studies [24][25][26][27][28][29][30][31][32][33][34] (5%) reported different RTS times based on type of sport (eg, non-contact at 4 months and contact at 6 months).…”
Section: Timementioning
confidence: 99%
“…First, Wang et al and Wierer et al reported that patients >40 years of age would achieve comparable clinical outcomes after ACL reconstruction as younger patients. 17 , 18 Second, the authors the present study attempted to clarify the laxity of ACL injured knee according to age and location of the femoral attachment of ACL remnant tissue.…”
Section: Methodsmentioning
confidence: 98%